Malaysian Studies: Looking Back, Moving Forward by Abdul Rahman Embong, Persatuan Sains Sosial Malaysia - Mustafa Kamal Anuar (Kajian Malaysia, 2011)
This book is essentially a compilation of speeches, public statements, press statements, essays and interviews related to the immediate past president of the Malaysian Social Science Association (MSSA, established on 14 September 1978), Professor Abdul Rahman Embong. But more than that, this book provides an insight into the history of social sciences in general and the MSSA in particular via author Rahman Embong's writings.